Hubungan Iklim Organisasi dan Komitmen Terhadap Organisasi Dengan Mempertimbangkan Lama Kerja (Studi Pada Staf Pengajar dan Pendukung di Universitas Swasta X Jakarta) - Sukma Rani; Hendriati Agustiani; Maya Rosmawati Ardiwinata; R. Urip Purwono (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
This study aim is to find the correlation between organizational climate and organizational commitment with considering the employee’s tenure. The subjects of this study were 94 employees of X private university. This study used purposive sampling. Researcher used organizational climate scale and organizational commitment scale which has been developed by Susanty (2012). The result of this study using Spearman Correlation showed r = 0,694 with p = 0,000 0,05. It shows that there is a signigicant and positive correlation between organizational climate and organizational commitment. The result from considering the employee’s tenure is a significant and positive correlation between organizational climate and organizational commitment from two tenure groups of participants. From these results, it is concluded that the hypothesis stating there is a positive correlation between organizational climate and organizational commitment is acceptable